Prussian Blue‐Derived Atomic Fe/Fe3C@N‐Doped C Catalysts Supported by Carbon Cloth as Integrated Air Cathode for Flexible Zn‐Air Batteries - Zihan Wang; Jing Ren; Guoqiang Ling; Junjie Guo; Yongkang Lv; Rui‐Peng Ren (Advanced Science)
Abstract The development of an integrated air cathode with superior oxygen reduction reaction (ORR) performance is fundamental to flexible zinc‐air batteries (ZABs) for wearable electronics. Herein, a self‐assembled metal‐organic framework (MOF)‐derived strategy is proposed to prepare a atomic Fe/Fe3C@N‐doped C catalysts supported by carbon cloth (CC) catalyst for use as an air cathode of flexible ZABs. The Prussian Blue precursor, which self‐assembles on the surface of the carbon cloth due to electrostatic attraction, is critical in achieving the uniform dispersion of catalysts with high density loading on carbon cloth substrates. The hollow cubic structure, N‐doped carbon layer coating, and the integrated electrode design can provide more accessible active sites and facilitate a rapid electron transfer and mass transport. Density functional theory (DFT) calculation reveals that the electronic interactions between the Fe‐N4 and Fe3C dual active sites can optimize the adsorption‐desorption behavior of oxygen intermediates formed during the ORR. Consequently, the Fe/Fe3C@N‐doped C/CC exhibits an excellent half wave potential (E1/2 = 0.903 V) and superior long‐term cycling stability in alkaline environments. With excellent ORR performance, ZABs and flexible ZABs based on Fe/Fe3C@N‐doped C/CC air cathode demonstrate excellent overall electrochemical performance in terms of open circuit voltage, maximum power density, flexibility, and cycling stability.